The Role of Bureaucracy in the Implementation of Education Policy - Noviyanti, Wita; Agus Alif Humaydiy; Masduki Duriyat (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Education is a strategic sector in national development that requires the implementation of effective and well-structured policies. In this context, bureaucracy plays a vital role as the implementer, connector, and controller of policy execution from the central government to the school level. This paper aims to examine the role of bureaucracy in the implementation of education policy and analyze the challenges encountered in the process. The method used is a literature review with a qualitative descriptive approach. The findings indicate that bureaucracy is involved in program planning, resource distribution, policy implementation monitoring, and stakeholder communication. However, the implementation process still faces obstacles such as limited human resources, bureaucratic inefficiency, weak inter-agency coordination, and resistance to change at the grassroots level. To enhance the effectiveness of education policy implementation, it is necessary to strengthen bureaucratic capacity, simplify administrative procedures, and improve the accountability of education personnel. By optimizing the role of bureaucracy, the goals of national education policy can be achieved more effectively.